2-({4-[3-Methyl-3-(2,4,6-trimethylphenyl)cyclobutyl]-3H-thiazol-2-ylidene}hydrazonomethyl)benzene-1,4diol ethanol solvate - Yüksektepe, C; Soylu, MS; Saraçoglu, H; Yilmaz, I; Çukurovali, A; Çaliskan, N (Int Union Crystallography, 2005)
In the title compound, C24H27N3O2S center dot C2H6O, the dihedral angle between the least-squares planes of the 2,5-dihydroxybenzene ring and the mesityl group is 78.59 (6)degrees. An intramolecular O-H center dot center dot center dot N hydrogen bond is observed in the molecular structure. Centrosymmetrically related molecules are linked by N-H center dot center dot center dot O intermolecular hydrogen bonds to form a dimer. The dimers are interlinked by O-H center dot center dot center dot O and O-H center dot center dot center dot N intermolecular hydrogen bonds involving the ethanol molecule of crystallization to form chains along the a axis.
Keywords: Complexes